Inducing private finance to water supply and inland water transport using spillover tax revenues - Naoyuki Yoshino; Umid Abidhadjaev; Masaki Nakahigashi (Asian Development Bank Institute (ADBI), 2019)
This paper discusses suggested ways to bring private sector finance into water supply and inland water transport. Typically, such water projects rely only on user charges as sources of revenues. For example, ships using inland waterways have to pay user charges to the government for port maintenance. However, water supply and inland water transport projects also attract new businesses to the region and bring about development of new residential areas. This leads to a rise in revenues from property tax, business tax, income tax, and sales tax due to expansion of new businesses. In the past, all these increased tax revenues were collected by the government; they were not returned to the infrastructure investors. If part of these increased tax revenues, for example 50%, were returned to investors in water supply and inland water transport, revenues would rise while keeping user charges as low as possible. Inland water transport thus can create a positive impact on farmers, helping them to sell their products to the market by reducing user charges. Inland water transport also can bring tourism into the region by increasing hotel businesses, restaurants, and so on. This in turn will increase tax revenues in the region. Insurance, pension funds, and bank loans could be provided to water supply and inland water transport projects if part of such increased tax revenues were returned to the investors every year. An increase in private investment in the water supply and inland water will expand services to a much larger area than if the government were to provide finance alone. Economic growth will be accelerated and income disparities will be mitigated by creating job opportunities for many people in the region.
Keywords: H54; O18; 330; water supply; inland water transport; private finance; infrastructure investment; spillover tax revenues